THE RELATIONSHIP BETWEEN PREGNANT WOMEN'S ATTITUDES AND COMPLIANCE WITH INTEGRATED ANTENATAL CARE VISITS AT SINGOSARI HEALTH CENTER, MALANG REGENCY - Dwijayanti, Serly; Mansur , Herawati; Yuliawati , Dwi (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Integrated Antenatal Care is a 10 T standardized pregnancy examination to facilitate the development of mother and baby and detect complications. The purpose of this study was to analyze the relationship between attitude and compliance of pregnant women to conduct Integrated Antenatal Care  visits. Methods: The research design was correlation analytic with cross sectional approach. The population was all pregnant women who made Integrated Antenatal Care  visits in July 2023, using purposive sampling technique obtained a sample of 44 respondents. The instrument used was a questionnaire of the attitude of pregnant women and a checklist of pregnant women's data from the Maternal & Child Health book and cohort. Chi Square test is used to analyze the relationship between variables. Research results: Most of the 59% of pregnant women have a negative attitude towards Integrated Antenatal Care  and 61% of pregnant women are not compliant with Integrated Antenatal Care .  The results of chi square analysis of the relationship between the attitude of pregnant women with compliance with Integrated Antenatal Care  visits obtained the result of p = 0.000 (α < 0.05). Conclusion: There is a relationship between the attitude of pregnant women and compliance with Integrated Antenatal Care  at Singosari Health Center, Malang Regency. The results of the study can be used as a basis for developing or comparing other factors that affect the compliance of pregnant women to conduct Integrated Antenatal Care  visits.